2006
DOI: 10.1111/j.0030-1299.2006.14145.x
|View full text |Cite
|
Sign up to set email alerts
|

Small habitat size and isolation can promote species richness: second‐order effects on biodiversity in shallow lakes and ponds

Abstract: Contemporary ecological landscape planning is often based on the assumption that small isolated habitat patches sustain relatively few species. Here, we suggest that for shallow lakes and ponds, the opposite can be true for some groups of organisms. Fish communities tend to be poor or even absent in small isolated lakes. However, submerged vegetation is often more abundant in such waterbodies. As a consequence of low fish biomass and high vegetation abundance, the richness of aquatic birds, plants, amphibians … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

21
274
2
6

Year Published

2007
2007
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 368 publications
(303 citation statements)
references
References 54 publications
21
274
2
6
Order By: Relevance
“…Field studies show that macrophyte richness is related to several lake variables, including lake area, altitude, shoreline complexity, connectivity, trophic state, conductivity and water and sediment quality (Rorslett, 1991;Murphy, 2002;Makela et al, 2004;Declerck et al, 2005;Scheffer et al, 2006;Geurts et al, 2008). This makes macrophyte species richness generally hard to predict (Edvardsen & Okland, 2006).…”
Section: Macrophyte Biodiversitymentioning
confidence: 99%
See 1 more Smart Citation
“…Field studies show that macrophyte richness is related to several lake variables, including lake area, altitude, shoreline complexity, connectivity, trophic state, conductivity and water and sediment quality (Rorslett, 1991;Murphy, 2002;Makela et al, 2004;Declerck et al, 2005;Scheffer et al, 2006;Geurts et al, 2008). This makes macrophyte species richness generally hard to predict (Edvardsen & Okland, 2006).…”
Section: Macrophyte Biodiversitymentioning
confidence: 99%
“…An explanation for the counterintuitive relationship between isolation and species richness is that isolated ponds frequently lack benthivorous fish, which create turbid conditions through their foraging in sediment. Isolated ponds that lack those fish have higher richness of macrophyte species because they become turbid less easily if habitat conditions deteriorate (Scheffer et al, 2006). However, at high macrophyte productivity, moderate levels of disturbance may actually increase macrophyte diversity.…”
Section: Macrophyte Biodiversitymentioning
confidence: 99%
“…Studies involving pond area have yielded conflicting results, with some demonstrating strong influences on plants and invertebrates ) and others demonstrating weak (if any) effects on macroinvertebrate richness (Oertli et al 2002;Søndergaard et al 2005). This break from conventional species-area relationships may be due to second-order effects in the form of ecological interactions which vary between ponds of differing connectivity and dimensions (Scheffer et al 2006). The relatively small size of ponds also renders them vulnerable to drying out, and drying has been shown to have an effect on alpha diversity of ponds , with variations between the biological communities of temporary and permanent ponds (Collinson et al 1995).…”
Section: Physical Correlates Of Pond Species Richnessmentioning
confidence: 99%
“…Recent studies have revealed their importance for aquatic biodiversity (Pyke 2005, Dimitriou et al 2006, Scheffer et al 2006, EPCN 2007 because, despite their small size, they disproportionately contribute to regional diversity, e.g., when compared to streams, large rivers, or lakes (Oertli et al 2002, Williams et al 2004, Karaus et al 2005. To date, the structure of biological communities in ponds was mostly studied on the basis of taxonomic composition (Sahuquillo et al 2007, Céréghino et al 2008.…”
Section: Introductionmentioning
confidence: 99%